Effect of Disturbances of Zinc and Copper on the Physical and Mental Health Status of Patients with Alcohol Dependence - M. Ordak; E. Bulska; K. Jablonka-Salach; A. Luciuk; M. Maj-Żurawska; H. Matsumoto; T. Nasierowski; M. Wojnar; J. Matras; E. Muszynska; M. Bujalska-Zadrozny (Biological Trace Element Research, 2018)

Carp edema virus in Polish aquaculture – evidence of significant sequence divergence and a new lineage in common carp Cyprinus carpio (L.) - M Matras; E Borzym; D Stone; K Way; M Stachnik; J Maj‐Paluch; M Palusińska; M Reichert (Journal of Fish Diseases, 2017)
Fish samples initially collected by local veterinarians on the common and koi carp farms in Poland between 2013 and 2015 as part of a KHV surveillance programme, when the water temperature was between 16 and 26 °C, and were also tested for CEV by qPCR . A partial 478 nucleotide fragment of the 4a gene was subsequently generated from 17 qPCR ‐positive common carp Cyprinus carpio samples from 36 farm sites tested during the period. Sequence alignments and analysis revealed the presence of CEV in Poland both in common carp as well as in koi carp farms, and phylogenetic analysis assigned the Polish CEV sequences into three distinct genogroups. A lineage which includes the original sequences obtained from koi carp in Japan (genogroup II ) included sequences from both koi carp and common carp, and the second lineage (genogroup I) contained sequences from common carp only. A third lineage (genogroup III ) which was more closely related to the genogroup II also consisted of sequences from common carp only. The latter represents a lineage of CEV not previously described in the literature.

Sorption of Cd2+ ions onto zeolite synthesized from perlite waste - M. Król; E. Matras; W. Mozgawa (International Journal of Environmental Science and Technology, 2016)

Genetic diversity of spring viraemia of carp virus isolates based on the glycoprotein gene - J Maj‐Paluch; E Borzym; M Matras; M Stachnik; M Reichert (Journal of Fish Diseases, 2016)

Down‐regulation of MHC class I mRNA expression in the course of KHV infection - M Reichert; E Borzym; M Matras; J Maj‐Paluch; M Stachnik; M Palusinska (Journal of Fish Diseases, 2016)

First isolation of hirame rhabdovirus from freshwater fish in E urope - E Borzym; M Matras; J Maj‐Paluch; M Baud; C De Boisséson; C Talbi; N J Olesen; L Bigarré (Journal of Fish Diseases, 2014)
A rhabdovirus was isolated in cell culture inoculated with tissue material from diseased grayling, T hymallus thymallus (L.), originating from a fish farm affected by a mortality episode in P oland. Diagnostics tests showed that the virus was not related to novirhabdoviruses known in E urope, nor to vesiculovirus‐like species, except p erch rhabdovirus ( PR hV) with which it shared moderate serological relations. However, RT ‐ PCR with PR hV probes gave negative results. To identify the virus, a random‐priming sequence‐independent single primer amplification was adopted. Surprisingly, two of the obtained sequences exhibited a high identity (>99%) with h irame rhabdovirus ( HIRRV ), a novirhabdovirus usually found in fish in marine A siatic countries, for instance J apan, C hina and K orea. The full‐length sequence of the phosphoprotein gene (P) demonstrated a higher identity of the present isolate with HIRRV from C hina compared with the K orean isolate. An identical viral sequence was also found in brown trout, S almo trutta trutta L., affected by mortalities in a second farm in the same region, after a likely contamination from the grayling farm. To our knowledge, this is the first report of HIRRV in E urope, and in two hosts from fresh water that have not been described before as susceptible species.